An infectious SARS-CoV-2 B.1.1.529 Omicron virus escapes neutralization by therapeutic monoclonal antibodies - VanBlargan, Laura A.; Errico, John M.; Halfmann, Peter J.; Zost, Seth J.; Crowe, James E.; Purcell, Lisa A.; Kawaoka, Yoshihiro; Corti, Davide; Fremont, Daved H.; Diamond, Michael S. (Nature medicine, 2022)
The emergence of the highly transmissible B.1.1.529 Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is concerning for antibody countermeasure efficacy because of the number of mutations in the spike protein. In this study, we tested a panel of anti-receptor-binding domain monoclonal antibodies (mAbs) corresponding to those in clinical use by Vir Biotechnology (S309, the parent mAb of VIR-7831 (sotrovimab)), AstraZeneca (COV2-2196 and COV2-2130, the parent mAbs of AZD8895 and AZD1061), Regeneron (REGN10933 and REGN10987), Eli Lilly (LY-CoV555 and LY-CoV016) and Celltrion (CT-P59) for their ability to neutralize an infectious B.1.1.529 Omicron isolate. Several mAbs (LY-CoV555, LY-CoV016, REGN10933, REGN10987 and CT-P59) completely lost neutralizing activity against B.1.1.529 virus in both Vero-TMPRSS2 and Vero-hACE2-TMPRSS2 cells, whereas others were reduced (COV2-2196 and COV2-2130 combination, ~12-fold decrease) or minimally affected (S309). Our results suggest that several, but not all, of the antibodies in clinical use might lose efficacy against the B.1.1.529 Omicron variant. New in vitro data suggest that the new SARS-CoV-2 Omicron variant is likely to escape neutralization by most therapeutic antibodies currently available.